Physiotherapy Research Priorities in Switzerland: Views of the Various Stakeholders. (17th March 2015) - Nast, Irina; Tal, Amir; Schmid, Stefan; Schoeb, Veronika; Rau, Barbara; Barbero, Marco; Kool, Jan
Abstract: Background and purpose: Research priorities, defined by multiple stakeholders, can proximally facilitate the coordination of research projects and national and international cooperation and distally further improve the quality of physiotherapy practice. The aim of this study was therefore to establish physiotherapy research priorities in Switzerland considering multiple stakeholders' opinions. Methods: A mixed methods design was chosen. For a qualitative identification of physiotherapy research topics, 18 focus group discussions and 23 semi‐structured interviews/written commentaries were conducted. For the quantitative analysis, 420 participants prioritized research topics using a two‐round Delphi questionnaire survey. The following stakeholder groups were surveyed in the German‐speaking, French‐speaking and Italian‐speaking regions of Switzerland: physiotherapy researchers, practitioners and educators, representatives of patient organizations, public health organizations, health insurers, physicians, nurses, occupational therapists and other health professionals, as well as physical educators. Results: The top five overall physiotherapy research priorities identified were as follows: physiotherapy treatment, physiotherapy assessment and diagnosis, prevention, physiotherapist–patient interaction and physiotherapy professional education at the bachelor level. With regard to diagnostic groups, the highest priorities were placed on musculoskeletal disorders, neurology, orthopaedics, geriatrics and ergonomics/occupational health. Consensus was moderate to high, and only few differences between stakeholder groups were revealed. Discussion: Research directly related to physiotherapy treatment is of highest priority. It should focus on diagnostic groups related to chronicity in anticipation of demographic changes. Multidisciplinary networks for research and practice, alongside sound coordination of research projects, should increase the impact of physiotherapy research. An accurate dissemination of research priorities, defined and supported by multiple stakeholder groups, might strengthen their impact on research and practice. Copyright © 2015 John Wiley & Sons, Ltd.